Coxsackievirus A6 Induces Necroptosis for Viral Production - Zhang, Shuxia; Yu, Xiaoyan; Meng, Xiangling; Huo, Wenbo; Su, Ying; Liu, Jinming; Liu, Yumeng; Zhang, Jun; Wang, Shaohua; Yu, Jinghua (Frontiers in Microbiology, 2020)
Hand, foot, and mouth disease (HFMD) is a febrile exanthematous disease with typical or atypical symptoms. Typical HFMD is usually caused by enterovirus 71 (EV71) or coxsackievirus A16, while atypical HFMD is usually caused by coxsackievirus A6 (CA6). In recent years, worldwide outbreaks of CA6-associated HFMD have dramatically increased, although the pathogenic mechanism of CA6 is still unclear. EV71 has been established to induce caspase-dependent apoptosis, but in this study, we demonstrate that CA6 infection promotes a distinct pathway of cell death that involves loss of cell membrane integrity. Necrostatin-1, an inhibitor of necroptosis, blocks the cell death induced by CA6 infection, but Z-DEVD-FMK, an inhibitor of caspase-3, has no effect on CA6-induced cell death. Furthermore, CA6 infection up-regulates the expression of the necroptosis signaling molecule RIPK3. Importantly, necrostatin-1 inhibits CA6 viral production, as assessed by its ability to inhibit levels of VP1 protein and genomic RNA and infectious particles. CA6-induced necroptosis is not dependent on the generation of reactive oxygen species; however, viral 3D protein can directly bind RIPK3, which is suggestive of a direct mechanism of necroptosis induction. Therefore, these results indicate that CA6 induces a mechanism of RIPK3-dependent necroptosis for viral production that is distinct from the mechanism of apoptosis induced by typical HFMD viruses.